Tests of resistance of vulcanized butyl rubber membrane to permeation by organic solvents mixtures - Krzemińska, S. (Polimery, 2022)
The results of investigations of the resistance of membranes (0.2 mm thickness) of butyl rubber vulcanizates to permeation by organic solvents (as individuals or binary mixtures) commonly used in paint and varnish manufacture (Fig. 1) were presented. Normalized value of membrane' breakthrough time for the substance used (Table 1) has been taken as a resistance criterion. The results of permeation by mixtures of acetone/toluene or toluene/n-butyl acetate show that breakthrough time of individual solvents significantly differ from break-through time of the same solvents in mixtures in various compositions. It was found increasing part of toluene (showing very short breakthrough time) accelerates permeation of the other component i.e. shortens measured breakthrough time. However, mixtures of ethyl acetate/n-butyl acetate, independently on the composition, do not show significant differences in breakthrough time values of individual solvents and their mixtures. The results of tests were interpreted on the basis of dipole moments of solvents, their molecules' spatial dimensions and generalized three-dimensional solubility parameters.